Differences in the Structural Components Influence the Pumping Capacity of Marine Sponges - Dahihande, Azraj S.; Thakur, Narsinh L. (Frontiers in Marine Science, 2021)
Marine sponges are important sessile, benthic filter feeders with a body plan designed to pump water efficiently. The sponge body plan generally consists of mineral spicules, gelatinous mesohyl, and the pores and canals of the aquiferous system. These structural components have stark differences in compressibility, mass, and volume; therefore, their proportion and distribution are likely to affect sponge morphology, anatomy, contraction, and finally the pumping capacity. We examined seven demosponge species (from high spicule skeleton contents to no spicules) commonly found along the central west coast of India for structural components, such as total inorganic contents (spicule skeleton and foreign inclusions), body density, porosity, and mesohyl TEM for the high microbial abundance/low microbial abundance status. Additionally, we estimated the sponge pumping rate by measuring the excurrent velocity, the abundance of individual pumping units and cells, i.e., choanocyte chambers and choanocytes, and also carried out a morphometric analysis of aquiferous structures. The excurrent velocity and the oscular flow rates showed a positive relationship with the oscular crosssectional area for all the study species. The inorganic spicule contents by their weight as well as volume formed a major component of tissue density and higher proportions of spicules were associated with reduced aquiferous structures and lower pumping rate. The ash mass% and the ash free dry weight (AFDW %) in the sponge dry mass showed separate and distinct associations with aquiferous system variables. For example, the number of choanocytes per chamber showed a wide difference between the studied species ranging from 35.02 ± 2.44 (C. cf. cavernosa) to 120.35 ± 8.98 (I. fusca) and had a significant positive relationship with AFDW% and a negative relationship with ash mass%. This study indicates that the differences in the proportions of structural components are closely related to sponge gross morphology, anatomy, and probably body contractions, factors that influence the sponge pumping capacity.